EFFECTIVENESS OF RISK - FOCUSED TECHNIQUE AND LIFE COACHING SKILLS ON OFFENDING BEHAVIOUR REDUCTION AMONG INMATES OF REMAND HOMES IN SOUTHWESTERN NIGERIA (2014)
Offending behaviour among adolescents is on the increase, and is of concern to social welfare practitioners and the criminal justice system because such behaviour represents a significant measure of adolescents well-being and future personality. Often, adolescents are at logger-heads with significant others when they engage in different types of activities like stealing, truancy, bullying, murder and gangsterism. The consequence is collision with the criminal justice system for discipline, correction and rehabilitation. Correctional psychologists have called for special intervention programmes like Risk-Focused Technique (RFT) and Life Coaching Skills (LCS) in rehabilitating such offending adolescents. Previous studies have concentrated more on opinionated studies with a view to finding solutions to the causal factors of offending behaviour among adolescents than on experimenting with social intervention programmes. This study, therefore, investigated the effectiveness of Risk-Focused Technique (RFT) and Life Coaching Skills (LCS) on the reduction of offending behaviour among inmates of remand homes in Southwestern Nigeria. The moderating effects of gender and self esteem were also determined. The study adopted pretest-posttest, control group, quasi-experimental design with a 3x2x3 factorial matrix. Participants were assigned into RFT, LCS and Control groups. Treatment lasted eight weeks. Fifty-two participants (41 males and 11females) out of (52 males and 16 females) were purposively selected from three remand homes in Oyo (19), Ogun (24) and Osun (9) States. The samples were stratified into two experimental conditions - RFT and LCS and the control group. Two instruments were used: Self-Report Measures of Offending Behaviour Scale (r = 0.78) and Rosenberg Self-esteem Scale (r = 0.77). Seven hypotheses were tested at a 0.05 level of significance. Data were analysed with Analysis of Covariance, and Multiple Classification Analysis. There was significant main effect of treatment on the reduction of offending behaviour of participants (F2,39 = 135.991; ?2 = 0.88). The experimental participants: LCS (x = 43.83) and RFT (x = 48.99), performed better than the control group (x = 57.37) on offending behaviour reduction. Also, self-esteem had a significant main effect on the reduction of participants offending behaviour (F2,39 = 3.827; ?2 = 0.16). The experimental participants: LCS(x = 42.35) and RFT (x = 38.28) had higher self-esteem than those in control group(x = 20.98). However, gender had no significant main effect on reduction of offending behaviour. There was also no significant interaction effect of treatment and gender on participants offending behaviour. Further, there was no significant interaction effect of treatment and self-esteem on offending behaviour of the participants. However, there was significant interaction effect of self-esteem and gender on participants offending behaviour (F2,39 = 5.991; ?2 = 0.24). Finally there was no significant interaction effect of treatment, gender and self-esteem on participants offending behaviour. Risk-focused technique and life coaching skills were effective in the reduction of offending behaviour among inmates of remand homes in Southwestern Nigeria. Therefore, it is recommended that the two interventions should be utilised by officials of youth agencies and social welfare practitioners involved in correctional psychology.